COMPARATIVE STUDY OF URBAN FARMING PRACTICES AROUND THE WORLD: EFFORTS TO SUPPORT FOOD SECURITY AND ENVIRONMENTAL CONSERVATION - Indra Jaya Wiranata (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Accelerated urbanization, climate crisis, and increasing food insecurity in various parts of the world have prompted cities to seek innovative strategies to ensure the sustainability of food systems while preserving the environment. One approach that is increasingly being adopted is urban agriculture, which combines food production with ecosystem services. This study conducts a comparative analysis of various urban agriculture practices in seven countries—Iran, the United Kingdom, Argentina, South Korea, Singapore, Zimbabwe, and New Zealand—to assess their impact on food security and environmental conservation. Each region has different forms of practices such as community gardens, rooftop gardens, vertical farming, permaculture, and community agroecology, which are implemented to enhance social solidarity, community empowerment, energy efficiency improvements, and food sovereignty. Government support varies from weak to very strong, with Singapore and South Korea providing comprehensive policy interventions, while Zimbabwe and Iran tend to rely on community-led initiatives. Contributions to food security are particularly notable in regions with high food vulnerability, such as Iran and Zimbabwe, as well as through national-scale food security strategies, such as in Singapore. On the other hand, contributions to environmental conservation include the provision of public green spaces, climate change mitigation, urban heat island cooling, carbon sequestration, water and soil resource conservation, and biodiversity enhancement. This study employs a qualitative approach using a comparative study method based on literature review. Data were collected from various scientific publications, policy reports, and relevant case studies, then analyzed to identify similarities, differences, and success factors of urban agriculture practices in each country. The analysis focused on the relationship between the form of practice, the level of policy support, and its impact on food security and environmental sustainability. The findings of this study confirm that the effectiveness of urban agriculture is determined by the alignment of practice forms with the local context, adequate policy support, and its integration into sustainable development strategies, thereby functioning as a strategic instrument in building a resilient and environmentally friendly urban food system.